Legal protection of personal data of banking customers in Indonesia: Human rights perspective - Rama, Bagus Gede Ari; Rusmana, I Putu Edi (Institute Of computer Science (IOCS), 2024)
The digital era has rapidly transformed various sectors, including the banking sector. The use of the internet in banking transactions has made transactions easier, faster, and more efficient. However, the efficiency of these transactions comes with risks. The implementation of banking activities in Indonesia is accompanied by the precautionary principle, as the government is obligated to provide direction and guidance on economic growth and create a healthy business climate. Mobile banking has experienced a significant increase in Indonesia, with banks like Bank BRI, Bank BNI, Bank Mandiri, and Bank BCA experiencing significant increases in users. However, the rise in mobile banking users is also accompanied by threats related to data leakage. The banking sector has experienced rampant cyber attacks in 2024, indicating that customer data security is vulnerable to hacking and misuse. This study aims to discuss the nature of legal protection for personal data of banking customers from a human rights perspective and the model of legal protection for banking customer data in Indonesia.